Adsorptive stripping voltammetry as a method of analysis of some pharmaceutical and other purine derivatives - Raqi M. Shubietah (1995)
Adsorptive stripping voltammetry (AdSV) is a recent technique (initially named by Lam, Kalvoda and Kopanica in 1983) in which there is generally a nonelectrolytic accumulation (adsorption) of the determinand followed by a cathodic reductive or anodic oxidative scan. In this work, a hanging mercury drop electrode (HMDE) was used to accumulate several purine derivatives with and without the addition of Cu(lI) in a suitable buffer (usually Britton-Robinson, pH 7.5). In the presence of copper(lI) the copper(l) purine complex was usually accumulated at about -0.1 V. Some of the compounds studied (i.e dimenhydrinate, theophylline, guanine and azathioprine) can be determined as free compounds (i.e with no Cu(lI) added) after accumulation at potentials ranging from 0 to -0.2 V versus Ag/AgCI reference electrode. The determination of these compounds was made after optimising pH, buffer constituents, accumulation potential and accumulation time. The addition of Cu(lI) to these purines makes possible accumulation at shorter accumulation times , and improves the detection limits. For example, the detection limit of azathioprine in the presence of Cu(lI) is as low as 2x10-10 M. Both differential-pulse polarography (DPP) and DP-AdCSV (differential pulse adsorptive cathodic stripping voltammetry) were used in the determination of theophylline and azathioprine in their dosage forms (tablets). The relative standard deviations for the determination of the pharmaceutical purines in their tablets were 3.0%. 4.2% and 1.3% for the measured concentrations of dimenhydrinate(1.5x10-7 M) , theophylline(2x10-7 M) by AdSV ; and azathioprine(2x10-6 M) by DPP, respectively . Other purines (eg xanthine,1,3-dimethyluric acid and some methylguanines) did not give peak currents useful for their determination. The addition of Cu(lI) was necessary to obtain satisfactory peak currents for these purines. At low copper(lI) concentrations (Le.< 10-6 M), it is suggested that the purines form Cu(l) complexes which are adsorbed at the HMDE surface: Cu(lI) + Cu(O) + 2 L ~ 2 Cu(I)-L adsorbed